A look inside the nerve – Morphology of nerve fascicles in healthy controls and patients with polyneuropathy. Issue 12 (December 2017) - Grimm, Alexander; Winter, Natalie; Rattay, Tim W.; Härtig, Florian; Dammeier, Nele M.; Auffenberg, Eva; Koch, Marilin; Axer, Hubertus
Highlights: Normal values of nerve fascicles might be helpful in analysis and treatment of nerve disorders. Fascicle enlargement occurs in inherited and inflammatory neuropathies with distinct distribution. Fascicle pattern analysis and - ratios might be suitable to differentiate several polyneuropathies. Abstract: Objective: Polyneuropathies are increasingly analyzed by ultrasound. Summarizing, diffuse enlargement is typical in Charcot-Marie Tooth type 1 (CMT1a), regional enlargement occurs in inflammatory neuropathies. However, a distinction of subtypes is still challenging. Therefore, this study focused on fascicle size and pattern in controls and distinct neuropathies. Methods: Cross-sectional area (CSA) of the median, ulnar and peroneal nerve (MN, UN, PN) was measured at predefined landmarks in 50 healthy controls, 15 CMT1a and 13 MMN patients. Additionally, largest fascicle size and number of visible fascicles was obtained at the mid-upper arm cross-section of the MN and UN and in the popliteal fossa cross-section of the PN. Results: Cut-off normal values for fascicle size in the MN, UN and PN were defined (<4.8 mm 2, <2.8 mm 2 and <3.5 mm 2 ). In CMT1a CSA and fascicle values are significantly enlarged in all nerves, while in MMN CSA and fascicles are regionally enlarged with predominance in the upper arm nerves. The ratio of enlarged fascicles and all fascicles was significantly increased in CMT1a (>50%) in all nerves (p < 0.0001), representingdiffuse fascicle enlargement, and moderately increased in MMN (>20%), representingdifferential fascicle enlargement (enlarged and normal fascicles at the same location) sparing the peroneal nerve (regional fascicle enlargement ). Based on these findings distinct fascicle patterns were defined. Conclusion: Normal values for fascicle size could be evaluated; while CMT1a features diffuse fascicle enlargement, MMN shows regional and differential predominance with enlarged fascicles as single pathology. Significance: Pattern analysis of fascicles might facilitate distinction of several otherwise similar neuropathies.